The economic history of Bengal : from plassey to the permanent settlement - Sinha, Narendra Krishna (Calcutta : Firma KLM, 1962)
Economics
2004-09-12
Keywords: Economic history; Zamindari system; Settlement; Economic - Social history; Bengal